2021
DOI: 10.3803/enm.2021.1034
|View full text |Cite
|
Sign up to set email alerts
|

Association between Iodine Intake, Thyroid Function, and Papillary Thyroid Cancer: A Case-Control Study

Abstract: Background: This study aimed to assess the effects of iodine intake, thyroid function, and their combined effect on the risk of papillary thyroid cancer (PTC) and papillary thyroid microcarcinoma (PTMC).Methods: A case-control study was conducted including 500 community-based controls who had undergone a health check-up, and 446 overall PTC cases (209 PTC and 237 PTMC) from the Thyroid Cancer Longitudinal Study. Urinary iodine concentration (UIC), was used as an indicator of iodine intake, and serum for thyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 45 publications
(75 reference statements)
2
24
0
Order By: Relevance
“…consequences on human health and associated with the presence of TBN and TMN[4][5][6][7][8][61][62][63][64]. In present study elevated level of I in thyroid tissue adjacent to TBN and TMN was found in comparison with "normal" thyroid.…”
supporting
confidence: 46%
See 1 more Smart Citation
“…consequences on human health and associated with the presence of TBN and TMN[4][5][6][7][8][61][62][63][64]. In present study elevated level of I in thyroid tissue adjacent to TBN and TMN was found in comparison with "normal" thyroid.…”
supporting
confidence: 46%
“…However, it was found that TN is a frequent disease even in those countries and regions where the population is never exposed to iodine shortage. Moreover, it was shown that iodine excess has severe consequences on human health and associated with the presence of TN [5][6][7][8]. It was also demonstrated that besides the iodine deficiency and excess many other dietary, environmental, and occupational factors are associated with the TN incidence [3,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limited number of individual studies in the meta-analysis and the different amounts of iodine intake, the findings appeared to be consistent with our results. In contrast, several studies have indicated the potentially harmful effects of excessive iodine intake regarding hypothyroidism, as excessive intake triggers the Wolff-Chaikoff effect [38][39][40][41]. Therefore, excessive intake of seaweed and iodine or not requires further recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Iodine not taken up by the thyroid is excreted from the body in urine [88]. Due to its role in thyroid hormone synthesis, dietary iodine intake is closely related to thyroid function [89,90]. Both iodine deficiency and iodine excess have been associated with an increased risk of thyroid disorders including iodide-induced hyperthyroidism, autoimmune thyroid disease, iodine-induced hypothyroidism [90,91].…”
Section: Iodine and Selenium Intakes And Glucose Metabolismmentioning
confidence: 99%